The Essentials of Employee Engagement in Organizations - Simon, Simeon S. (Journal of Contemporary Research in Management (JCRM), 2013)
This paper throws light on the importance, need and the focus of employee engagement, and the factors enhancing employee engagement level in the organizational set up. Employee Engagement is an emerging phenomenon which should be well taken care of by the managers in the present scenario of business environment. The managers have to be keen whether employees are engaged or disengaged in their work setting, since disengagement or alienation can be the central problem of workers for their lack of commitment and motivation. Meaningless work is often associated with apathy and detachment from ones works. In such conditions, individuals are thought to be estranged from their selves. Other Research using a different resource of engagement (involvement and enthusiasm) has linked it to such variables as employee turnover, customer satisfaction – loyalty, safety and to a lesser degree, productivity and profitability criteria. Engagement is linked to three essential forces in the organization - attrition, productivity & profitability. Ultimately the productivity is what is expected by the company from employees. An engaged employee carry out what is expected of him, having his focus and goal clear and brings success to the organization. Profitability is the result of actively engaged work force. What company look for are committed and sincere employees who can perform their job efficiently with all role clarity. Here this paper throws light on the essentials of employee engagement, how shared visions enhance engagement level and the steps to be taken by a firm to build engagement.